Realizing Demographic Dividends in the Republic of Congo - Skoufias, Emmanuel (World Bank, Washington, DC, 2020)
Between 2005 and 2015 the population living in poverty decreased substantially due to increased government revenues from high oil prices and the expansionary spending that accompanied these revenues. However, despite the recent substantial reduction in poverty, results commensurate with its level of GDP and natural resource endowment have yet to be achieved. Furthermore, during the years of strong economic growth, the economy created jobs, but these were offset by the population growth. The analysis in this report lays the groundwork for more effective actions accelerating the demographic transition in Congo and facilitating the realization of the potential demographic dividend. With the right set of policies in place, the change in the structure of the population during the demographic transition offers an opportunity to capitalize on the “demographic dividend” that can help generate additional growth in the future.